The Immediate Effects of Expert and Dyad External Focus Feedback on Drop Landing Biomechanics in Female Athletes: An Instrumented Field Study - Kelly A. Leonard; Janet E. Simon; Jae Yom; Dustin R. Grooms (North American Sports Medicine Institute, 2021)
# Background Anterior Cruciate Ligament (ACL) injury prevention interventions have used trained experts to ensure quality feedback. Dyad (peer) feedback may be a more cost-effective method to deliver feedback to athletes. # Purpose To determine the immediate effects of dyad versus expert feedback on drop landing kinematics and kinetics in female athletes. # Study Design Cohort study # Setting College gymnasium # Methods Two teams (one female basketball and one female volleyball), from a local college, were team randomized to dyad feedback (volleyball team) or expert feedback (basketball team) (13 expert, 19±0.87years, 1.7±0.09m, 68.04±7.21kg) (10 dyad 19.4±1.07years, 1.73±0.08m, 72.18±11.23kg). Participants completed drop vertical jumps at two different time points (pre- and post-feedback). Knee flexion and abduction displacement were assessed with Inertial Measurement Units (IMUs) and vertical ground reaction force (vGRF) was assessed with a force plate during the landing phase of the drop vertical jump and compared across groups and condition (pre- and post-feedback) with a repeated measures ANCOVA *a priori* α <0.02 was set for multiple tests conducted. # Results There were no significant differences between groups for flexion displacement. There was a significant change pre- to post- (decrease 4.65˚ p=0.01) in abduction displacement, with no group effect. There was a significant interaction of group by condition (p=0.01) for vGRF with no difference between groups before feedback (p>0.05). Between groups there was a decrease of vGRF in the expert group (difference 0.45 N\*bw-1, p=0.01) at post-feedback relative to dyad. Within the expert group there was a significant difference between pre- and post-feedback (difference 0.72 N\*bw-1, p=0.01), while the dyad group did not change pre- to post-feedback (difference 0.18 N\*bw-1, p=0.67). # Conclusion Movement screening experts giving real-time feedback were successful in improving key injury-risk kinematics and kinetics in female athletes, while dyad feedback only improved kinematics, indicating that expert feedback may be needed to ensure changes in kinematics and kinetics. # Level of Evidence 2